1981
DOI: 10.1104/pp.68.4.831
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Carbon Dioxide on Ethylene Production and Action in Intact Sunflower Plants

Abstract: A continuous flow system was used to study the interactions between carbon dioxide and ethylene in intact sunflower (Helanthus aNua L.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
41
0

Year Published

1982
1982
2009
2009

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 15 publications
9
41
0
Order By: Relevance
“…Increased production of ethylene in response to enhanced levels of CO2 has been demonstrated for detached leaves and leaf discs of cocklebur (15), intact sunflower plants (6,12), tobacco leaf discs (1,2,18), and detached senescing oat leaves (14). The effect is obtained when CO2 is supplied either directly as a gas or indirectly as bicarbonate, and no increase in ethylene production ' is obtained when CO2 is removed with a KOH trap (15,18).…”
mentioning
confidence: 87%
“…Increased production of ethylene in response to enhanced levels of CO2 has been demonstrated for detached leaves and leaf discs of cocklebur (15), intact sunflower plants (6,12), tobacco leaf discs (1,2,18), and detached senescing oat leaves (14). The effect is obtained when CO2 is supplied either directly as a gas or indirectly as bicarbonate, and no increase in ethylene production ' is obtained when CO2 is removed with a KOH trap (15,18).…”
mentioning
confidence: 87%
“…Using these techniques, we have recently reported that an increase in the concentration of CO2 in the atmosphere surrounding the sunflower plants increased the rate of ethylene production (5). The change in rate of ethylene production was evident within the first few minutes of the carbon dioxide treatment.…”
mentioning
confidence: 99%
“…The ethylene measurements were made by enclosing the plant in a specially designed glass cuvette (3), in a continuous flow system using hydrocarbon free air (6). The environmental parameters and the techniques used for purification of air, CO2 treatment and ethylene measurement were the same as described in our earlier papers (3,5,6). The air mixtures containing different concentrations of CO2 were also passed through the purification system before entering the cuvette.…”
Section: Introductionmentioning
confidence: 99%
“…To date, there has been no report on ethylene measurements from single attached leaves incubated in an open system. In the present work, shoots or single leaves of intact plants were used for measurements of ethylene production.It is known that C02 affects the rate of ethylene evolution from tissues (6,11,16), presumably acting on the conversion of ACC4 to ethylene (16,19). However, there has been no report on the effect of CO2 on the possible differences in ethylene production among tissues at different stages of development.…”
mentioning
confidence: 99%
“…It is known that C02 affects the rate of ethylene evolution from tissues (6,11,16), presumably acting on the conversion of ACC4 to ethylene (16,19). However, there has been no report on the effect of CO2 on the possible differences in ethylene production among tissues at different stages of development.…”
mentioning
confidence: 99%